Evaluation of the BOD POD for estimating percent body fat in collegiate track and field female athletes: a comparison of four methods - Bentzur, K. M.; Kravitz, L.; Lockner, D. W. (The Journal of Strength and Conditioning Research, 2008)
This investigation examined the accuracy of the BOD POD on a group of Division I collegiate track and field female athletes (N = 30). Hydrostatic weighing (HW) was used as the gold standard method. Body density (Db) values obtained from the BOD POD (DbBP) were compared with those determined by HW (DbHW). Both Db values were converted to percent body fat (%BF) using the Siri equation for comparison. Percent body fat values obtained from the BOD POD (BFBP) were also compared with those obtained from dual-energy X-ray absorptiometry (DXA, BFDXA) and skinfold (SF, BFSF). The validity of the BOD POD was assessed using repeated-measures analysis of variance (ANOVA), and the relationship between the methods was examined through Pearson correlation. Average DbBP was 0.00890 g[middle dot]cm-3 lower (p < 0.05) than DbHW, resulting in a significant overestimation of %BF (p < 0.05) by the BOD POD. Values for BFDXA and BFBP also differed significantly (p < 0.05). On the other hand, BFSF and BFBP were not significantly different. The correlation between percent body fat values obtained from HW (BFHW) and BFBP was good (r = 0.88, SEE = 2.30) as well as between BFSF and BFBP (r = 0.85, SEE = 2.05). Conversely, the correlation between BFDXA and BFBP was poor (r = 0.25, SEE = 5.73). The strong correlation between BFBP and BFHW presented here suggests that the BOD POD has the potential to be used as a body composition analysis tool for female athletes. The advantages of the BOD POD over HW encourage further investigation of this instrument. However, the fact that the BOD POD and SF results did not differ significantly might suggest that the SF could be used in its place until a better rate of accuracy for this instrument is established.